Sugary drink advertising expenditure across Australian media channels 2016-2018 - Ashleigh Haynes; Megan Bayly; Helen Dixon; Alison McAleese; Jane Martin; Yan Jun Michelle Chen; Melanie Wakefield (Elsevier, 2021)
Abstract Objective: The aim of this study was to describe advertising expenditure for sugary drinks compared with alternative cold non‐alcoholic beverages (artificially sweetened beverages, plain water, plain milk) between 2016 and 2018 across Australian media channels. Methods: Monthly estimates of advertising expenditure for non‐alcoholic beverages were obtained from Nielsen Media and aggregated by product type and media. Results: Total sugary drink advertising expenditure between 2016 and 2018 ($129.5M) significantly exceeded expenditure on artificially sweetened drinks ($23.26M), plain water ($14.27M), and plain milk ($31.30M). Television and out‐of‐home advertising accounted for the largest share of sugary drink advertising (45%, 35%). Expenditure on out‐of‐home advertising was more heavily dominated by sugary drinks (75%) than advertising in all media combined (65%). Sugary drink advertising peaked in warmer months and was lowest in August. Soft drinks (26%), flavoured milks (24%) and energy drinks (21%) accounted for the majority of sugary drink advertising. Conclusions: Cold non‐alcoholic beverage advertising in Australian media is dominated by the advertising of sugary drinks. Implications for public health: Restricting unhealthy beverage advertising on television and out‐of‐home media may be most effective initially. However, comprehensive restrictions capturing a broader range of media and settings would be optimal to prevent displacement and limit advertising reach and exposure.